1991
DOI: 10.1128/cmr.4.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Rhodococcus equi: an animal and human pathogen

Abstract: Recent isolations of Rhodococcus equi from cavitatory pulmonary disease in patients with AIDS have aroused interest among medical microbiologists in this unusual organism. Earlier isolations from humans had also been in immunosuppressed patients following hemolymphatic tumors or renal transplantation. This organism has been recognized for many years as a cause of a serious pyogranulomatous pneumonia of young foals and is occasionally isolated from granulomatous lesions in several other species, in some cases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
560
2
42

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 594 publications
(614 citation statements)
references
References 134 publications
10
560
2
42
Order By: Relevance
“…When incubated aerobically at 37°C, R. equi grows efficiently in the majority of nonselective culture media, including media used in mycobacteria isolation and produces irregular, smooth and mucoid colonies that turn a shade of salmon pink to yellow after a week of growth (Prescott 1991 tures in the initial identification of different nocardioform genera (Christopher & Bruno 2002). In general, R. equi is biochemically non-reactive, has no proteolytic activity and fails to oxidize or ferment carbohydrates, with the exception of glucose, which is oxidized by R. equi in 14 days.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When incubated aerobically at 37°C, R. equi grows efficiently in the majority of nonselective culture media, including media used in mycobacteria isolation and produces irregular, smooth and mucoid colonies that turn a shade of salmon pink to yellow after a week of growth (Prescott 1991 tures in the initial identification of different nocardioform genera (Christopher & Bruno 2002). In general, R. equi is biochemically non-reactive, has no proteolytic activity and fails to oxidize or ferment carbohydrates, with the exception of glucose, which is oxidized by R. equi in 14 days.…”
mentioning
confidence: 99%
“…R. equi is strictly aerobic, catalase positive, oxidase negative and mostly urease positive. R. equi produces soluble "equi factors" that are associated with phospholipase and cholesterol oxidase activity and interact with phospholipase D of Listeria ivanovii to induce complete haemolysis of sheep erythrocytes (Prescott 1991).…”
mentioning
confidence: 99%
“…Sixteen of the 20 glutamines of this gene were encoded by TAA or TAG. It has been shown that TAA and TAG encode glutamine instead of causing termination in the genes of several ciliates [12]. The predicted UbcP1 protein contains the conserved active site region consensus pattern…”
Section: Resultsmentioning
confidence: 99%
“…For instance, they have evolved separate somatic and germ-line functions using two distinct nuclei, macro-and micronuclei, respectively [12]. In this respect, they can be used as a model system for multicellular organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Rhodococcus equi pneumonia is an important disease of foals most commonly characterized by chronic progression associated with development of large pulmonary abscesses 1. Treatment of R. equi pneumonia is prolonged and expensive, and prevention is limited because transfusion of hyperimmune plasma is incompletely effective,2 chemoprophylaxis is inconsistently effective3, 4 and may promote antimicrobial resistance,5 and no effective vaccine is currently available 6.…”
mentioning
confidence: 99%